A simple strategy for culturing morphologically-conserved rat hypothalamic tanycytes - De Francesco, Pablo Nicolás (2017)
Hypothalamic tanycytes are specialized bipolar ependymal cells that line the floor of the third ventricle. Given their strategic location, tanycytes are believed to play several key functions including being a selective barrier and controlling the amount of hypothalamic-derived factors reaching the anterior pituitary. The in vitro culture of these cells has proved to be difficult. Here, we report an improved method for the generation of primary cultures of rat hypothalamic tanycytes. Ependymal cultures were derived from tissue dissected out of the median eminence region of 10-day-old rats and cultured in a chemically defined medium containing DMEM:F12, serum albumin, insulin, transferrin and the antibiotic gentamycin. After 7 days in vitro, -30% of the cultured cells exhibited morphological features of tanycytes as observed by phase contrast or scanning electron microscopy. Tanycyte-like cells were strongly immuno-reactive for vimentin and dopamine-cAMP-regulated phospho-protein (DARPP-32) and weakly immune-reactive for glial fibrillary acidic protein. Tanycyte-like cells displayed a stable negative resting plasma membrane potential and failed to show spiking properties in response to current injections. When exposed to fluorescent beads in the culture medium, tanycyte-like cells exhibited a robust endocytosis. Thus, the present method effectively yields cultures containing tanycyte-like cells that resemble in vivo tanycytes in terms of morphologic features and molecular markers as well as electrical and endocytic activity. To our knowledge, this is the first protocol that allows the culturing of tanycyte-like cells that can be individually identified and that conserve the morphology of tanycytes in then- natural physiological environment.